Beyond the Lavender Scare: LGBT and Heterosexual Employees in the Federal Workplace. (2nd January 2017) - Federman, Peter Stanley; Rishel Elias, Nicole M.
Abstract : Lesbian, gay, bisexual, and transgender (LGBT) identities within the workplace have recently gained greater attention as significant demographic categories. A key question that emerges from the limited scholarship on LGBT employment in the federal government is whether there is a distinction between the experiences of employees within federal security agencies, defined here as the five major agencies that provide civilian support to the defense and military structures of the United States, and employees of other federal agencies. Using data from the 2013 Employee Viewpoint Survey, this article addresses the following questions: How does sexual orientation and/or gender identity as self-reported in the 2013 EVS impact employee perceptions of personal safety and security, job satisfaction, and diversity issues, and how do these perceptions vary between employees of the major security agencies and other federal agencies? The article shows that across the federal government employees are reasonably satisfied with diversity issues in the workplace, with no appreciable difference between those in security and nonsecurity agencies. However, current programs and policies intended to foster and institutionalize diversity are viewed as ineffective and should be improved through new policies and programs.